Avaliação do desempenho do biorreator de vórtices de Taylor na expansão de células estromais mesenquimais - Gil, Liseth Viviana González (Universidade Federal de São Carlos, 2019)
Interest in the use of mesenchymal stromal cells (MSCs) has increased in the last 10 years because of the increasing discovery of its special characteristics for the treatment of diseases through cell therapy or tissue engineering. Despite being in the majority of postnatal organs and tissues, the amount of MSCs required to initiate any clinical treatment is insufficient and therefore the necessity of its in vitro expansion. Cultivation systems with the use of microcarriers and bioreactors, such as the stirred tank, are presented as the immediate proposal, allowing to obtain high cellular densities in a 3D environment. However, the stirred tank presents some limitations related to the distribution of hydrodynamic forces within the bioreactor and the difficulty in controlling the size of aggregates formed during cultivation, ultimately affecting the process yield of obtaining viable cells. A highly promising bioreactor proposal for presenting low and more homogeneous shear stresses, satisfactory mass transfer and ease of scaling is the Taylor Vortex Flow Bioreactor (TVFB). In a preliminary study, the BEVT, with a work volume of 60 mL, was promising in the cultivation of a line of immortalized CEMs attached to microcarriers, presenting controlled sizes of cellular aggregates (<400 μm) under conditions of low shear stresses and with sufficient oxygen transfer. In this sense, the present work involved the construction and the study of a BEVT with a work volume of 100 mL, for the cultivation of primary CEMs currently used in clinical treatments. Thus, the additional evaluation of important hydrodynamic parameters, such as the minimum velocity of suspension of particles (Ns1) and time of mixing (θm) in different conditions of rotation, were approached for two internal cylinder configurations, named in this study as round and deformed. In this evaluation the BEVT with the deformed inner cylinder presented better performance and was chosen in the culture studies. For this configuration Ns1 values between 70 and 90 rpm were obtained using a concentration of 1 to 3 g of microcarregages/mL and a maximum θm of 21±2,2 seconds for a rotation speed of 50 rpm. Cultivation of umbilical cord derived CEMs cultures and Cultispher®S 1 and 3 g / L adipose tissue using the 10% SFB alpha MEM culture medium confirmed the best modulation of the aggregation presented in the BEVT, compared to the Spinner flask, under low shear conditions, confirmed by the LDH enzyme activity, and with adequate oxygen transfer, obtaining factors of expansion of up to 17 times of viable and functional CEMs. Thus, these results present the BEVT as a very promising alternative for the cultivation of large-scale CEMs for cell therapy.
Evaluation of Taylor vortex flow bioreactor performance for mesenchymal stromal cell expansion
Keywords: Células estromais mesenquimais (CEMs) humanas; Biorreator de escoamento em vórtices de Taylor (BEVT); Agregados em sistemas de cultivo agitado baseado em microcarregadores; Critério de suspensão (Ns1); Tempos de mistura (θm); Human mesenchymal stromal cells (hMSCs); Microcarriers; Taylor Vortex Flow Bioreactor; Oxygen transfer; Shear stress; Mixing time; Minimum agitation speed for complete solid suspension (Ns1); Células estromales mesenquimais; Bioreactor de flujo en vórtices de Taylor; Microcargadores; Tiempo de mezcla; ENGENHARIAS::ENGENHARIA QUIMICA::OPERACOES INDUSTRIAIS E EQUIPAMENTOS PARA ENGENHARIA QUIMICA